Association between hemorrhoid and risk of coronary heart disease: A nationwide population-based cohort study. Issue 31 (August 2017) - Chang, Shih-Sheng; Sung, Fung-Chang; Lin, Cheng-Li; Hu, Wei-Syun
Abstract : Abstract: The purpose of the study was to address the association between hemorrhoid and the subsequent risk of coronary heart disease (CHD) development. This retrospective cohort study used reimbursement claims data from the Longitudinal Health Insurance Database 2000 in Taiwan. Thirty-three thousand thirty-four patients with hemorrhoids and 132, 136 age-, gender-, and index year matched controls between 2000 and 2010 were identified. Cox model was performed to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of CHD development for the hemorrhoid cohort compared with the nonhemorrhoid cohort. During a follow-up period of 12 years, the overall incidence rate of CHD was 9.91 per 1000 person-years in the hemorrhoid patients and was 1.36-fold higher than in the nonhemorrhoid cohort (7.28 per 1000 person-years) with an adjusted hazard ratio (aHR) of 1.27 (95% CI = 1.21–1.34). Moreover, compared with the nonhemorrhoid patients without these comorbidities, among patients with hemorrhoids, those with any 2 comorbidities were at a significantly increased risk of CHD (HR = 7.12, 95% CI = 6.61–7.67; P  < .001), followed by those with any 1 comorbidity (HR = 3.23, 95% CI = 2.94–3.54; P  < .001). We found that hemorrhoid patients had a 1.27-fold higher risk of CHD compared with those without hemorrhoids after adjusting for the potential confounding factors.